2021
DOI: 10.1055/s-0041-1735580
|View full text |Cite
|
Sign up to set email alerts
|

Single Ophthalmology Program Trends in Resident Surgical and Research Productivity by Gender, Underrepresented Minority Status, and Welcoming a Child

Abstract: Objective The aim of the study is to identify differences for cataract surgery, total procedural volume, and publication rates between residents by gender, underrepresented minority (URM) status, and welcoming a child during ophthalmology residency. Design This is a retrospective, cross-sectional study. Participants A total of 89 residents graduating from 2002 to 2020 at a single program were included. Methods A multiple linear regression model was created to determine factors pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Of 4077 retrieved studies, we reviewed 154 full-text articles, with 91 eligible studies published between 1995 and 2022 (Figure). Most studies (57 [62.6%]) were published in or after 2018 (eTable 1 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 4077 retrieved studies, we reviewed 154 full-text articles, with 91 eligible studies published between 1995 and 2022 (Figure). Most studies (57 [62.6%]) were published in or after 2018 (eTable 1 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (57 [62.6%]) were published in or after 2018 (eTable 1 in the Supplement). Eighty-seven studies were cross-sectional, and 4 studies were cohort. In the risk of bias assessment, 12 had low risk of bias (good), 68 were moderate (fair), and 11 were high (poor) (eTables 2 and 3 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…reported female and UiM residents performed fewer major surgical cases than male or non‐UiM residents, with a discrepancy also noted when comparing male UiM and male non‐UiM groups. However, a similar study in ophthalmology found no difference in cataract surgeries or procedures for women and UiM residents 10 . EM differs from these specialties given the unique environment with unpredictable procedural opportunities and smaller teams.…”
Section: Introductionmentioning
confidence: 88%
“…However, a similar study in ophthalmology found no difference in cataract surgeries or procedures for women and UiM residents. 10 EM differs from these specialties given the unique environment with unpredictable procedural opportunities and smaller teams. To our knowledge, no prior literature has evaluated how these biases and variabilities may be operating within EM procedural education.…”
Section: Introductionmentioning
confidence: 99%